Mystic love poems in the poetry of Atika Al-Khazraji - المدرس المساعد فرح غانم صالح حمید البیرماني (College of Education for Women, 2019)
We deal with this essay about religious mystic poetry of Atika Al- Khazraji. We think she imitates Rabia Al-Adawiyya. We do not deny that our poetess lived in a conservative society although she lives in reality a liberal life, so she tries to satisfy her society. In fact these mystic poems are pure love. Poems in men. This double standard behavior is quite clear in women's poems in the Arab world of this era.